2013
DOI: 10.3892/ijmm.2013.1262
|View full text |Cite
|
Sign up to set email alerts
|

Gua Lou Gui Zhi decoction exerts neuroprotective effects on post-stroke spasticity via the modulation of glutamate levels and AMPA receptor expression

Abstract: Spasticity is one of the most physically debilitating disabilities following stroke and may slow down the potential success of rehabilitation. Glutamate and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors have been shown to play a crucial role in spasticity following cerebral ischemia/reperfusion (I/R) injury. Gua Lou Gui Zhi decoction (GLGZD) is a well-known traditional Chinese formula that has long been used clinically in China to treat muscular spasticity following stroke, epilepsy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The recognition that cerebral stroke is a manifestation of chronic progressive inflammation has had great influence on the development of therapeutic and preventative strategies (13,14) and as such, the Chinese formula may be a promising therapeutic strategy for ameliorating strokeinduced inflammatory pathological events. GLGZD has been reported to be an effective treatment for stroke in clinical practice and in animal experiments (15)(16)(17). In our previous study in vitro, we demonstrated that GLGZD water extract exerts anti-inflammatory effects in LPS-induced microglial cells mediated by the nuclear factor-κB (NF-κB) sinaling pathway (9); however, the precise molecular mechanisms responsible for its neuroprotective effects have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition that cerebral stroke is a manifestation of chronic progressive inflammation has had great influence on the development of therapeutic and preventative strategies (13,14) and as such, the Chinese formula may be a promising therapeutic strategy for ameliorating strokeinduced inflammatory pathological events. GLGZD has been reported to be an effective treatment for stroke in clinical practice and in animal experiments (15)(16)(17). In our previous study in vitro, we demonstrated that GLGZD water extract exerts anti-inflammatory effects in LPS-induced microglial cells mediated by the nuclear factor-κB (NF-κB) sinaling pathway (9); however, the precise molecular mechanisms responsible for its neuroprotective effects have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that GLGZD treatment may inhibit spasticity resulting from ischemia by modulating glutamate levels in an experimental rat model (16). Furthermore, previous studies have suggested that GLGZD may exhibit anti-neuroinflammatory effects by suppressing microglial activation in a lipopolysaccharide (LPS)-induced microglial cell culture experimental model (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to investigate whether GLGZD exerted an anti-inflammatory and protective effect via the NF-κB signaling pathway, following cerebral ischemic injury. (16,17).…”
Section: Anti-inflammatory Effects Of Gualou Guizhi Decoction In Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship appeared to predominantly occur after exposure to both foot shock plus low temperature (Yuen et al 2009) and repeated immobilization, thereby emphasizing the importance of gene expression events on increased neuronal excitability and vulnerability (Schewendt and Jezová 2000). Moreover, the reduction of GluR1 mRNA expression capacities by CNQX concomitantly to the few neurodegenerative signals tends to s u p p o r t a n e u r o p r o t e c t i v e r o l e p l a y e d b y t h i s AMPAergic antagonist very likely as a consequence of reduced Ca 2+ influx, which constitutes a major factor responsible for the consolidation of synaptic silencing (Tanaka et al 2002;Huang et al 2013). In particular, the notable decrease of GluR1 mRNA levels with respect to those of GluR2 reported for HIP and COR might comprise a probable cause of diminished excitotoxic effects on GluR2-lacking Ca 2+ -permeable AMPARs in global ischemia (Higuchi et al 2000;Liu and Zukin 2007;Mele et al 2014).…”
Section: Discussionmentioning
confidence: 99%